Politik hukum: menakar kualitas reformasi regulasi dalam central oversight body - Ahmad Heru Romadhon; Sadjijono Sadjijono (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2021)
Improving the quality of regulatory reform in legal politics, which has implications for the direction of the formation of laws and regulations, demands counter-cultural changes within the regulatory institution itself. External controls and oversight are essential but not sufficient to overcome bureaucratic resistance and the growing philosophy of command and control. A number of approaches have been used through training and dissemination of information, repetition of writing on job descriptions and evaluation criteria, and building reform units, to support the functions of regulatory agencies. This research method is normative juridical, which emphasizes the study of literacy, laws and regulations, books and other related information sources. Juridical analysis shows clearly that bureaucratic reform should be seen as a long-term investment in building effectiveness, not just a solution to actual problems. This understanding will reduce the tendency for dysfunctional products to form regulations, due to the intervention of certain organizational or political interests. The change in the perspective of the bureaucrats in viewing the possible regulations will not be achieved in several decades without seriousness in improving the bureaucracy itself.Perbaikan kualitas reformasi regulasi dalam politik hukum yang berimplikasi pada arah pembentukkan peraturan perundang-undangan menuntut adanya perubahan counter cultural di dalam badan institusi pengaturan itu sendiri. Kontrol eksternal dan oversight merupakan hal yang penting tetapi tidak cukup untuk mengatasi resistansi birokrasi dan berkembangnya filosofi command and control. Sejumlah pendekatan telah dipergunakan melalui training dan desiminasi informasi, pengulangan penulisan pada job description dan kriteria evaluasi, serta membangun unit reformasi, untuk mendukung fungsi badan pengaturan. Metode penelitian ini adalah yuridis normatif yaitu menekankan pada studi literasi, peraturan perundang-undangan, buku dan sumber informasi lainya yang masih berkaitan. Analisis yuridis menunjukkan secara jelas bahwa reformasi birokrasi haruslah dipandang sebagai investasi jangka panjang dalam membangun efektifitas, bukan sekedar suatu solusi bagi masalah aktual. Pemahaman ini akan mengurangi kecenderungan disfungsional produk pembentukan peraturan, karena adanya intervensi kepentingan organisasi atau politik tertentu. Perubahan cara pandang para birokrat dalam memandang peraturan kemugkinan tidak akan tercapai dalam beberapa dekade tanpa keseriusan dalam memperbaiki tubuh birokrasi itu sendiri.